Lazer, juventude e ensino médio/técnico: um estudo sobre as tensões estabelecidas entre os processos de escolarização e lazer no Coltec - Ubiratan Santos Pouzas (2012)
This study aimed at understanding some issues involving education and leisure in Colegio Tecnico at UFMG (Coltec), which brought tension to the daily life of the school. Coltec is an institution that requires a great effort by young people as they face a large workload in double shift schools, moreover, requires extra classes activities. This context affected the daily lives of students in their search for experiences and leisure time. As a methodological framework, the work carried out, firstly, a literature review in order to contextualize the problem to be investigated. These readings allowed greater understanding of local dynamics and revealed how relationships between systems and subjects are established at the institution. Thus, on an initial study, the Coltec's area was observed, and then it was adopted the use of focus groups with some young people. From these methodological apparatuses it was possible to build five categories, which were explored in a dialogue concerning the issues raised in the study. The survey revealed that young people seek some "balance" between their duties at school and leisure experiences, which are carried out through the interstices of school. It was observed that they find gaps in time between classes and at lunch time, and from transgressive practices. The study also showed that young people take part in different cultural groups in the institution, marked by affinity, friendship, sociability and fellowship. Although students are endowed with certain freedom of action in Coltec, they are largely controlled by the Student Guild, which is the leading creator and developer of leisure events at school. Another aspect that was manifested in the research was the importance of greater scope and encouragement to the various types of knowledge that can be acquired in schools. Such knowledge goes beyond traditional disciplinary widely used and often pervade the scope of leisure, cultural and political life of the students.